Anti-VEGF in a Marathon Runner’s Retinopathy Case - Alexander Kahjun Soon; Paulo Ricardo Chaves de Oliveira; David Robert Chow (Case Reports in Ophthalmological Medicine)
Central retinal vein occlusion (CRVO) is one of the most common retinal vascular disorders. Intense exercise associated CRVO have been described in otherwise healthy young patients. We describe a case of a young male ultramarathoner who presented with a CRVO, presumably associated with dehydration, making part of a marathon runner’s retinopathy. Resolution of macular edema and subretinal fluid, with visual acuity improvement, was observed after 3 monthly injections of ranibizumab. Our case suggests that dehydration could be involved in the mechanism of CRVO in healthy young patients and ranibizumab may be an effective treatment option for marathon runner’s retinopathy.